Magnetic and structural properties of La1−xGdx CoO3 compounds - Panfilov, Anatoly S. (2023)
We present a study of magnetic and structural properties of La1−xGdxCoO3 compounds with x = 0, 0.2, 0.5 and 1. The Gd term in magnetic susceptibility obeys the Curie-Weiss law with antiferromagnetic interaction between the magnetic moments of Gd3+ ions. The value of the paramagnetic Curie temperature Θ is proportional to Gd content and for GdCoO3 it reaches Θ ' −5.5 K. The Co contribution, χCo(T), derived by subtracting the Gd term from the total susceptibility, shows a non-monotonous behavior which is originated by the temperature induced transition of Co3+ ions from the ground low spin state to a higher spin state separated by an energy ∆. The revealed strong increase in ∆ with increasing Gd content is presumably due to the manifestation of a chemical pressure upon replacing La with Gd having a smaller ionic size.